DETERMINATION OF THE REFRACTIVE INDEX OF DISPERSED LIQUIDS ACCORDING TO SNELL’S LAW - Akimova, Jumakhan Orazbaevna; Saburova, Surayyo Saparbaevna (SCIENCE and SOCIETY, 2026)
This scientific paper examines a laboratory experiment to determine the refractive index of various dispersive liquids (water, toluene, etc.) using Snell's law with a hollow prism. The minimum deviation angle method was employed, and refractive indices were calculated based on measured distances and angles. The obtained results are n_d ≈ 1.33 for water and n_d ≈ 1.50 for toluene, which agree with literature standard values within 1–2%. The simplified formulas derived from Snell's law under minimum deviation conditions in a prism served as the primary calculation tool. The phenomenon of dispersion is analyzed in detail, with experimental proofs based on Snell's law provided.
Keywords: dispersion; refractive index; Snell's law; hollow prism; minimum deviation angle; water; toluene